Highly efficient Al-Ti gel as a coagulant for surface water treatment: Insights into the hydrolysate transformation and coagulation mechanism. (1st August 2022) - Guo, Kangying; Wang, Zhining; Pan, Jingwen; Liu, Beibei; Wang, Yan; Yue, Qinyan; Gao, Yue; Gao, Baoyu
Highlights: The interaction between Al and Ti was explored by experiment and DFT calculation. TEA inhibited hydrolysis of Ti by coordinating with Ti to form CO-Ti bond. Ti was incorporated into the framework of Al hydrolysates to form Al-O-Ti bond. The high efficiency of Al-Ti gel benefited from the diversity of its hydrolysates. Al-Ti gel concurrently provided charge neutralization, adsorption and sweep effect. Abstract: In view of the insufficient coagulation efficiency of traditional inorganic coagulants, a series of Al-Ti gels with different Ti/triethanolamine (TEA), Ti/H2 O, and Ti/Al molar ratios were prepared by sol-gel process in this study. Fourier transform infrared (FTIR) spectra of the Al-Ti gels preliminarily confirmed the interaction between Al and Ti by detecting the appearance of the Al-O-Ti bond. The peak shift of the chemical bonds in X-ray photoelectron spectra (XPS) and the transformation of the hydrolysate species in the Al-Ti gels were analyzed to further explore the interaction mechanism between Al and Ti. It was found that moderate TEA could inhibit the hydrolysis of Ti precursors by taking up the coordination sites of H2 O to form a CO-Ti bond. Density functional theory (DFT) calculation results showed that Ti could be incorporated into the framework of aluminum hydrolysates to form an Al-O-Ti bond, and [Al2 Ti2 (OH)x (TEA)y (H2 O)8-x-y ] 14-x was the most possible copolymerization hydrolysate. Based on the above research results, the most efficient Al-Ti gel was selected and applied to the actual lake water treatment. The highest UV254 removal efficiency with the addition of Al-Ti gel was > 60%, nearly 25% higher than that of Ti gel. The hydrolysates of Al-Ti gel, such as TiO(OH)2(am), Al(OH)3(am), and [Al2 Ti2 (OH)x (TEA)y (H2 O)8-x-y ] 14-x, could remove organic matters through the incorporation of charge neutralization, adsorption, complexation, and sweeping effects. These results provide a new idea for studying the interaction mechanism between Al and Ti in composite coagulants, and have theoretical guiding significance to actual water treatment. Graphical abstract: Image, graphical abstract